The ATLAS inner detector trigger performance in pp collisions at 13 TeV during LHC Run 2 - Aad, Georges; Andrei, George Victor; Bartels, Falk; Czurylo, Marta; Dittmeier, Sebastian; Dunford, Monica; Franchino, Silvia; Klassen, Martin; Krishnan, Anjali; Mkrtchyan, Tigran; Napolitano, Fabrizio; Ott, Philipp; et al. (The European physical journal. C, Particles and fields, 2022)
The design and performance of the inner detector trigger for the high level trigger of the ATLAS experiment at the Large Hadron Collider during the 2016-2018 data taking period is discussed. In 2016, 2017, and 2018 the ATLAS detector recorded $$35.6~fb^{-1}$$, $$46.9~fb^{-1}$$, and $$60.6~fb^{-1}$$respectively of proton-proton collision data at a centre-of-mass energy of 13 TeV. In order to deal with the very high interaction multiplicities per bunch crossing expected with the 13 TeV collisions the inner detector trigger was redesigned during the long shutdown of the Large Hadron Collider from 2013 until 2015. An overview of these developments is provided and the performance of the tracking in the trigger for the muon, electron, tau and b-jet signatures is discussed. The high performance of the inner detector trigger with these extreme interaction multiplicities demonstrates how the inner detector tracking continues to lie at the heart of the trigger performance and is essential in enabling the ATLAS physics programme.